2010
DOI: 10.1016/j.jmb.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Occluding Loop of Cathepsin B Prevents Its Effective Inhibition by Human Kininogens

Abstract: The occluding loop of Cathepsin B prevents its effective inhibition by human kininogens Naudin, C.; Lecaille, F.; Chowdhury, S.; Krupa, J. C.; Purisima, E.; Mort, J.S.; Lalmanach, G.Contact us / Contactez nous: nparc.cisti@nrc-cnrc.gc.ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 81 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…Similar degradation of kininogens have been found in other inflammatory body fluids, like synovial and amniotic fluids, and blood plasma (for review: [30]). The lack of undamaged kininogens together with the presence of kininogen fragments ( circa 20–40 kDa) correlates with the recent demonstration that the inability of kininogens to inhibit cathepsin B (in contrast to cathepsins L and S) is associated with their extensive cleavage by cathepsin B [31]. We have also shown that Biot-LVG-CHN 2 , a cystatin C-derived activity-based probe, binds to sputum cysteine cathepsins.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar degradation of kininogens have been found in other inflammatory body fluids, like synovial and amniotic fluids, and blood plasma (for review: [30]). The lack of undamaged kininogens together with the presence of kininogen fragments ( circa 20–40 kDa) correlates with the recent demonstration that the inability of kininogens to inhibit cathepsin B (in contrast to cathepsins L and S) is associated with their extensive cleavage by cathepsin B [31]. We have also shown that Biot-LVG-CHN 2 , a cystatin C-derived activity-based probe, binds to sputum cysteine cathepsins.…”
Section: Resultssupporting
confidence: 79%
“…Our data also confirmed that significant amounts of cathepsins may escape regulation by their endogenous inhibitors. This, together with the recent demonstration that the poor inactivation of cathepsin B (unlike the tight-binding inhibition of cathepsins L and S) by kininogens is associated with their extensive cleavage by cathepsin B [31], indicates that cathepsin B is a major protease involved in this process in CF sputum. This is also true for several other inflammatory disorders (for review: [30]).…”
Section: Resultsmentioning
confidence: 87%
“…Lesser inhibition of cathepsin B is generally explained by the presence of an occluding loop in this protease which covers the active site and causes slow association of the inhibitor [29][30][31][32]. Likewise, the here characterized F. gigantica Stefin-2 can be classified as a type 1 cystatin based on its amino acid sequence (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, cathepsin B is poorly inhibited by kininogens due to the residues His110-His111 positioned within its occluding loop. The His110Ala cathepsin B mutant, unlike its His111Ala mutant, does not hydrolyze kininogens but forms a tight-binding complex [257].…”
Section: Mechanism Of Inhibition Of Cysteine Cathepsinsmentioning
confidence: 98%